Clinical Impact of Rapid Identification (ID) and Phenotypic Antimicrobial Susceptibility Testing (AST) by Accelerate Pheno™ System (AXDX) for Gram-negative (GNB) Bloodstream Infections. (4th October 2017) - Matic, Nancy; Willey, Barbara; Gascon, Bryan; Lee, Samantha; Koren, Vita; Surangiwala, Salman; Lo, Pauline; Mazzulli, Tony; Poutanen, Susan M
Abstract : Background: Laboratory turn-around-times (TATs) for identification (ID) and antimicrobial susceptibilities (AST) can delay prescription of adequate and/or optimal antimicrobial (ABX) therapy in septic patients leading to poor outcomes. The Accelerate Pheno™ system (Accelerate Diagnostics, USA) (AXDX) is a rapid ID and AST system with potential to improve TATs. Methods: 70 prospective non-duplicate blood cultures with Gram-negative bacilli were loaded onto AXDX. AXDX TATs were compared with TATs associated with current methods [ID by MALDI-TOF Vitek® MS (bioMérieux) using short-incubation plates, AST by Vitek® 2 (bioMérieux)]; modified current methods (calling MALDI ID and Vitek® 2 AST and releasing Vitek® 2 AST prior to purity plate review); and former methods (ID and AST by Vitek® 2), the latter determined by laboratory data review of 134 blood cultures from 2011. Impact of the change in TAT on ABX use was determined by chart review. Results: Gram stain, ID and AST results led to tailoring of ABX in 88.6% of patients impacting 22.9%, 31.4%, and 64.3% of patients at 2.5h, 19.0h, and 62.1h respectively post positive blood culture using current methods (Figures 1 and 2). AXDX generated the shortest ID and AST TATs with the potential to shorten the time to ABX tailoring due to ID and AST to 1.3h and 6.7h respectively. Calling ID and AST results directly to physicians or releasing AST results from Vitek® 2 prior to purity plate review would also have the potential to significantly improve time to ABX change compared with current methods. Conclusion: Among the methods compared, AXDX has the greatest potential impact on time to appropriate antibiotics following reports of ID and AST results in Gram-negative bacilli bloodstream infections. Calling ID or AST results directly to physicians could also improve time to ABX tailoring. Impact of engaging antimicrobial stewardship teams requires further study. Disclosures: S. M. Poutanen, Accelerate Diagnostics: Research Contractor and Scientific Advisor, Consulting fee and Research support